2006
DOI: 10.1520/gtj14004
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Filter-Paper and Suction-Plate Methods for Determining the Soil-Water Characteristic Curve of Undisturbed Colluvium Soils

Abstract: The relationship between matric or total suction and gravimetric water content, volumetric water content, or degree of saturation is denoted as the soil-water characteristic curve. This relationship has been widely used for predicting the engineering behavior of unsaturated soils. Residual and colluvium soils from tropical and subtropical regions often show bimodal-shaped soil-water characteristic curves, indicating that both micropores and macropores present in these soils govern the inflow and outflow of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Results showed a great variation of suction pressures over a small range of soil water contents, due to the greater retention capacity of the soil. SWRC with similar behavior to the soil used in this research were obtained by Feuerharmel et al (2006) and Portelinha & Zornberg (2017) for compacted fine lateritic soils.…”
Section: Experimental Programme 21 Materials and Samples Preparationmentioning
confidence: 52%
“…Results showed a great variation of suction pressures over a small range of soil water contents, due to the greater retention capacity of the soil. SWRC with similar behavior to the soil used in this research were obtained by Feuerharmel et al (2006) and Portelinha & Zornberg (2017) for compacted fine lateritic soils.…”
Section: Experimental Programme 21 Materials and Samples Preparationmentioning
confidence: 52%
“…Therefore, Gardner [41] proposed the filter paper method to determine the matrix suction of soil, which was adopted by the American Society of Materials and Tests (ASTM), with relevant standards. Moreover, Feuerharmel found that the filter paper method had high accuracy in determining the suction by comparing it with other matrix suction methods [42]. Since then, the filter paper method has been introduced into the field of geotechnical engineering and applied widely [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Given the air-entry value limitation of ceramic disk, the maximum suction imposed in PPM is generally 500 kPa or 1,500 kPa ( 8 ). FPM can cover the suction range of 5–3,000 kPa and the maximum suction measured by VEM can reach 368 MPa ( 6, 810 ). Therefore, the combination of different measurement techniques is usually adopted in SWCC tests ( 8 , 9 , 11 ).…”
mentioning
confidence: 99%